Targeted interference to laser acoustic reconnaissance - Zabolotnyi, V. I.; Kholiev, N. O.; Dovgal, V. S. (ХНУРЕ, 2025)
Methods of laser acoustic reconnaissance (LAR) of information disclosed at information activity objects (IAOs) are constantly being improved. Complexes of measures and means of protection against technical channels of information leakage (TCIL) of this nature are being developed and applied, which emphasizes the relevance of research on the topic of this work. The elements of the technical channel of information leakage are quantitatively analyzed: the parameters of win dow glass oscillation, the features of the operating principle of interference-type LAR, the lateral characteristics of the laser emission beam, and it is proposed to use them to create a targeting frequency band and direction of propagation of lateral emissions of the LAR beam by using corner reflectors in the infrared spectrum of optical vibrations. Постійно удосконалюються методи лазерних засобів акустичної розвідки (ЛЗАР) інформації, що озвучу ється на об’єктах інформаційної діяльності (ОІД). Розвиваються і застосовуються комплекси заходів і засобів захисту від технічного каналу витоку інформації (ТКВІ) цієї природи, що підкреслює актуальність досліджень за темою роботи. Кількісно проаналізовано елементи технічного каналу витоку інформації: параметри коливання шибки вікна, особливості принципу дії ЛЗАР інтерференційного типу, бічні характеристики променя випромінювання лазеру, запропоновано використовувати для створення прицільних по смузі частот і напряму поширення бічних випромінювань променя ЛЗАР за рахунок використання кутикових відбивачів в інфрачервоному діапазоні оптичних коливань.
Keywords: protection of voiced information; laser acoustic reconnaissance; targeted interference; лазерний засіб акустичної розвідки; прицільна перешкода